ROLE OF CT GUIDED BIOPSY IN CHARACTERIZATION OF PRIMARY AND SECONDARY PULMONARY LESIONS. - Dr. Sanjiv N Patel; Dr. Sapna S Patel; Dr. Khyati A Patel (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Computed tomography guided lung biopsy is invasive method for obtaining tissue samples from lung for histopathological analysis. This study evaluates the diagnostic yield and safety for CT guided lung biopsy. This is retrospective study of 40 patients with solitary or multiple pulmonary lesions who underwent CT guided biopsy and then tissue samples sent for histopathological analysis and correlation is done with diagnostic yield of 95%.  From which largest group is malignant lesion among which adenocarcinoma is more common followed by squamous cell carcinoma. No major complication is seen.